Analysis of referral channels on online news consumption - Husin, Husna Sarirah; Ruza, Nadiah (Journal of Computing Technologies and Creative Content, 2017)
When users visit a page, the browser records the referrer that sent the user to the page. If no referrer is recorded, it means that the user typed in the url of the page. Referrer can comes from various sites such as search engine site, social media sites or other sites. In this paper, we analyze how referrals have any impact on news consumption. We use a dataset of web server logs from an online newspaper for 14 days from 13-27 January 2017. We found that half of the referrals are from Facebook. In terms of contents, there is a significant strong relationship between referrer and article content. The Facebook referrals use Android devices to access the pages and Sunday has the highest number of page accessed. Our findings can be an input for the news organization in their strategy to position themselves as the leader in online news